SYSTEMATIC REVIEW OF NON-PHARMACOLOGICAL SLEEP INTERVENTIONS AMONG LONG-TERM CARE RESIDENTS. (11th November 2018) - Capezuti, E; Zadeh, R; Pain, K; Basara, A; Jiang, N; Krieger, A
Abstract: Disturbances in sleep and circadian rhythms are common among residents of long-term care facilities. In this systematic review, we aim to identify and evaluate the literature documenting the outcomes associated with non-pharmacological interventions to improve sleep among long-term care residents. The Preferred Reporting Items for Systematic Reviews guided searches of five databases (MEDLINE, Embase, CINAHL, Scopus, Cochrane Library) for articles reporting results of experimental or quasi-experimental studies conducted in long-term care settings (nursing homes, assisted-living facilities, or group homes) in which nighttime sleep was subjectively or objectively measured as a primary outcome. We categorized each intervention by its intended use and how it was administered. Of the 54 included studies evaluating the effects of 25 different non-pharmacological interventions, more than half employed a randomized controlled trial design (n=30); the others used a pre-post design with (n=11) or without (n=13) a comparison group. The majority of randomized controlled trials were at low risk for most types of bias, and most other studies met the standard quality criteria. The interventions were categorized as environmental interventions (n=14), complementary health practices (n=12), social/physical stimulation (n=11), clinical care practices (n=3), or mind-body practices (n=3). Although there was no clear pattern of positive findings, three interventions had the most promising results: increased daytime light exposure, nighttime use of melatonin, and acupressure. Non-pharmacological interventions have the potential to improve sleep for residents of long-term care facilities. Further research is needed to better standardize such interventions and provide clear implementation guidelines using cost-effective practices.